Data Warehouse Considerations: Investigating Indices And Hierarchical Denormalized Snowflakes (HDS) - Zaker, Morteza (2009)
This research proposes Hierarchical De-normalized Snowflake (HDS) as an alternative logical data model to achieve DW structure in order to improve the query performance.